EFEKTIVITAS PROGRAM CAKE KEBUN DALAM RANGKA PENCEGAHAN STUNTING DI KECAMATAN TELLULIMPOE - Sukarno Hatta (Universitas Mbojo Bima, 2022)
This study to determine the effectiveness of the cake kebun program in the context of preventing stunting in Tellulimpoe District. This research is a qualitative descriptive study with the aim of describing or thoroughly describing the effectiveness of the cake kebun program in the context of preventing stunting in Tellulimpoe District. Data was collected through observation, interviews and documentation. This research was conducted with research informants: 1) Head of Lappae Health Center, 2)Cake Kebun Innovator 3) Kalobba Village Head 4)Cake Kebun Team 5) Stunting Parents of Toddler. The results of this study indicate that 4 (four) indicators of program effectiveness which are the focus of research on the cake kebun program in the context of stunting prevention are quite effective. However, in its implementation there are various obstacles such as the problem of human resources that are still lacking, people who do not understand the need to prevent stunting from an early age, there are still toddlers who do not like cake kebun and there are still people who have not succeeded in cultivating Moringa because it failed to grow. Efforts made to overcome these problems include continuous socialization and promotion of the cake kebun program. conduct cooking demonstrations to several Integrated Healthcare Centre officers who are expected to be resource persons, socialize the benefits of Moringa leaves so that people have awareness to cultivate Moringa plants and continue to formulate cake kebun with variants favored by toddlers. Keywords: Effectiveness, Cake kebun, Stunting